2019
DOI: 10.5606/fng.btd.2019.010
|View full text |Cite
|
Sign up to set email alerts
|

1-metil-4-fenil-1,2,3,6-tetrahidropiridinin (MPTP) Parkinson hastalığı üzerindeki etkileri

Abstract: Parkinson's disease is a chronic movement disorder seen frequently in adults and caused by the destruction of dopaminergic neurons. Its symptoms are tremor, rigidity, balance disorder, and bradykinesia. The current medications of the disease cure the symptoms; none of them stops neurodegeneration. Various modellings are performed on experimental animals for Parkinson's disease research. The main substance used in these modellings is 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), a synthetic toxin. MPTP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…It was observed that a group of people using MPTP developed a syndrome that was irreversible and very similar to Parkinson's disease. [22] MPTP itself is not toxic. It can cross the blood-brain barrier and cause PD rapidly when it is injected.…”
Section: B) Parkinson Model Induced By 1-methyl 4-phenyl 1236-tetrahydropyridine (Mptp)mentioning
confidence: 99%
“…It was observed that a group of people using MPTP developed a syndrome that was irreversible and very similar to Parkinson's disease. [22] MPTP itself is not toxic. It can cross the blood-brain barrier and cause PD rapidly when it is injected.…”
Section: B) Parkinson Model Induced By 1-methyl 4-phenyl 1236-tetrahydropyridine (Mptp)mentioning
confidence: 99%
“…Fibroblast Growth Factor 21 (FGF-21) is a signaling protein with diverse biological functions in development and metabolism. FGF-21 levels increase with hunger, stress, mitochondrial dysfunction, obesity, mitochondrial myopathies, and aging [ 183 , 184 ]. Holm and colleagues found that FGF-21 levels, independently associated with IL-6 and lower muscle mass, were significantly higher in patients with cardiac cachexia than in healthy cohorts [ 185 ], suggesting that the increased plasma levels of FGF-21 in patients with cardiac cachexia correlate with inflammation and muscle wasting [ 185 ].…”
Section: Myokines As Potential Therapeutic Agents For Cancer Cachexiamentioning
confidence: 99%